Análisis del impacto proyectado de los impuestos sobre las bebidas azucaradas en la economía de colombiana según la ley 2277 del 2022 (2024)
The projected impact of taxes on sugary drinks is analyzed, highlighting the implementation of taxes based on their sugar content through Law 2277 of 2022. While recognizing the potential benefits of these taxes to reduce sugar consumption and prevent diseases, they are also recognized. raise concerns about its possible negative effects on the productive sector, employment and social equity. The tax behavior of taxpayers and the importance of a solid tax culture are examined. The proposed research will employ a qualitative approach to understand perceptions and behaviors related to sugary beverage taxes, including a comprehensive literature review and data collection through content analysis and other qualitative techniques such as newspapers, magazines, books.